Media - szanse, wyzwania i zagrożenia a potrzeba edukacji medialnej - Bereźnicka, Małgorzata (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2023)
This article refers to many levels of social life that have been transformed under the influence of mass media. The media, especially new media, have significantly influenced the functioning of individuals and social groups. The Internet is an undoubted and popularized breakthrough to which billions of users around the world have access. This article discusses the impact of the media on various aspects of our current reality with particular emphasis on the dimensions of communication, education, and the development of young people. Based on the certain subject related literature and the cited studies, the benefits of the increasing presence of media in our lives are characterized, as well as its negative and potentially harmful side effects. The negative effects are particularly disturbing in the context of the often unlimited use of modern technologies by children and adolescents. The problems presented in the article support the thesis concerning the necessity to implement media education, which should cover all generations. This article also advocates for the need for further research in this field.